Stress Akademik antara Laki-laki dan Perempuan Siswa School from Home - Wulida Rohmatillah; Nanik Kholifah (Ilmu Psikologi Universitas Yudharta Pasuruan, 2021)
The current spread of Covid-19 has forced the government to come up with a policy that forces students to study from home, which was eventually known as school from home. This study was conducted with the aim of knowing the differences in academic stress between male and female students from home schooling. The research method used is quantitative research. The subjects in this study were students of Darut Taqwa High School, which consisted of 30 male students and 30 female students. Data was collected using the academic stress scale. Based on the calculation of the validity test, obtained 30 valid items from the stress scale with an academic reliability coefficient of 0.99. The data obtained showed that the level of academic stress of male students who were in the low category was 30% and the medium category was 70%. Meanwhile, female students have academic stress levels which are in the medium category of 36.6% and the high category of 73.4%. Based on the results of data analysis using the t-test between groups, the results were 2,632 with a t-table of 5%, which was 2,000. This means that the results of this study indicate that there are differences in academic stress between male and female students studying from home.